Angiotensin II Receptor Blocker Associated With Less Outcome Risk in Patients With Acute Kidney Disease - Wu, Vin-Cent; Lin, Yu-Feng; Teng, Nai-Chi; Yang, Shao-Yu; Chou, Nai-Kuan; Tsao, Chun-Hao; Chen, Yung-Ming; Chueh, Jeff S; Chen, Likwang (Frontiers in Pharmacology, 2022)
OBJECTIVE: We aimed to explore the respective use of angiotensin-converting-enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB) on the outcomes of patients who could be weaned from dialysis-requiring acute kidney injury (AKI-D). METHODS: This case-control study enrolled 41,731 patients who were weaned from AKI-D for at least 7 days from Taiwan’s National Health Insurance Administration. We further grouped AKI-D patients according to ACEi and ARB use to evaluate subsequent risks of all-cause mortality and re-dialysis. The outcomes included the all-cause mortality and new-onset of end-stage kidney disease (ESKD; re-dialysis) following withdraw from AKI-D. RESULTS: 17,141 (41.1%) patients surviving AKI-D could be weaned from dialysis for at least 7 days. The overall events of mortality were 366 (48.9%) in ACEi users, 659 (52.1 %) in ARB users, and 6261 (41.3%) in ACEi/ARB non-users, during a mean follow-up period of 1.01 years after weaning from AKI-D. In regard to all-cause of mortality, predialysis ARB user had lower incidence than ACEi user (Hazard ratio (HR 0.82), p=0.017). Compared with ACEi/ARB nonusers, continuing ARB users had a significantly lower risk of long-term all-cause mortality (adjusted hazard ratio (aHR) 0.51, p=0.013) after propensity score matching. However, new users of ACEi at the acute kidney disease (AKD) period had a higher risk of re-dialysis after weaning than that of ACEi/ARB nonusers (aHR 1.82, p<0.001), whereas neither ACEi nor ARB users confronted significantly increased risks of hyperkalemia after weaning. CONCLUSIONS: Compared with patients without ACEi/ARB, those continuing to use ARB before the event and after weaning had lower all-cause mortality, while new users of ACEi at AKD had increased risk of re-dialysis. AKI-D patients continuing to use ACEi or ARB did not have higher risk of hyperkalemia. Future prospective randomized trials are expected to confirm these findings.